2014
DOI: 10.1111/ijn.12300
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of a specialist nursing service for adult patients with congenital heart disease

Abstract: The purpose of this study was to evaluate grown-up congenital heart (GUCH) patients' experiences and satisfaction with the delivery of a nurse specialist service, including perceived priorities and recommendations for future service delivery. A service evaluation utilizing descriptive, cross-sectional survey principles was conducted over a 2 year period. Postal questionnaires were sent to three patient cohorts (general adult n = 747; pregnancy n = 202; learning disability n = 72). Quantitative data were analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…However, by increasing quality-oriented and customer-based development in the health care sector of the country, through continuous feedback of patients' expectations and improvement of service provision, reforms in the quality of health care will be observed and the strengths and weaknesses of the sector can be determined [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, by increasing quality-oriented and customer-based development in the health care sector of the country, through continuous feedback of patients' expectations and improvement of service provision, reforms in the quality of health care will be observed and the strengths and weaknesses of the sector can be determined [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, high‐risk obstetric clinics may not necessarily be supported by grown‐up congenital heart (GUCH) teams (Abdin, ). Hatchett, McLaren, Corrigan, and Filer () reported on GUCH nursing services and found patients expressed enhanced feelings of safety in coping with the demands of pregnancy and a heart condition, as well as satisfaction with the information provided and continuity of care through important life transitions. Their research findings demonstrated the value and contribution of a specialist nursing service to women's experiences, particularly in terms of effective care coordination, monitoring and support (Hatchett et al, ).…”
Section: Multidisciplinary Management For Both Cardiac Groupsmentioning
confidence: 99%
“…Hatchett, McLaren, Corrigan, and Filer () reported on GUCH nursing services and found patients expressed enhanced feelings of safety in coping with the demands of pregnancy and a heart condition, as well as satisfaction with the information provided and continuity of care through important life transitions. Their research findings demonstrated the value and contribution of a specialist nursing service to women's experiences, particularly in terms of effective care coordination, monitoring and support (Hatchett et al, ). Given the recent reported deaths as a result of atherosclerosis and ischaemic‐related heart conditions, there also needs to be some discussion on the services required and available for women with ACS.…”
Section: Multidisciplinary Management For Both Cardiac Groupsmentioning
confidence: 99%
See 2 more Smart Citations